Adjuvant chemotherapy for stage I high-intermediate risk endometrial carcinoma with lymph-vascular invasion. Issue 9 (1st June 2022) - Nasioudis, Dimitrios; Oh, Jinhee; Ko, Emily M; Haggerty, Ashley F; Cory, Lori; Giuntoli, Robert L; Kim, Sarah H; Morgan, Mark A; Latif, Nawar A
Abstract : Objective: The goal of this study was to evaluate if addition of adjuvant chemotherapy to radiation therapy improves overall survival in patients with high-intermediate risk stage I endometrial carcinoma with lymphovascular invasion. Methods: Patients diagnosed between January 2010 and December 2015 with FIGO (International Federation of Gynecology and Obstetrics) stage I endometrioid endometrial carcinoma with lymphovascular invasion who underwent hysterectomy with lymphadenectomy and met the GOG-99 criteria for high-intermediate risk were identified in the National Cancer Database. Patients who received adjuvant radiotherapy with or without adjuvant chemotherapy (administered within 6 months of surgery) and had at least 1 month of follow-up were selected for further analysis. Overall survival was compared with the log-rank test following stratification by type of radiation treatment. A Cox model was constructed to control for a priori selected confounders. Results: A total of 2881 patients who met the inclusion criteria were identified; 2417 (83.9%) patients received radiation therapy alone while 464 (16.1%) received chemoradiation. Rate of adjuvant chemotherapy administration was comparable between patients who received vaginal brachytherapy alone (16.2%), and external beam radiation therapy (with or without vaginal brachytherapy) (15.8%), p=0.78. Rate of chemoradiation was higher for patients with grade 3 (28.8%) tumors compared with those with grade 2 (9.9%) and grade 1 (8.3%) tumors, p<0.001. After controlling for confounders for patients receiving external beam radiation, addition of chemotherapy was not associated with improved overall survival (HR 0.90, 95% CI 0.56 to 1.46). For patients receiving vaginal brachytherapy addition of chemotherapy was associated with better overall survival (HR 0.644, 95% CI 0.45 to 0.92). Benefit was limited to patients with grade 3 tumors, p=0.026; 4-year overall survival rate was 81.1% versus 74.9%. Conclusions: In patients with high-intermediate risk FIGO stage I endometrioid endometrial carcinoma and lymphovascular invasion, addition of chemotherapy to radiation therapy was associated with a survival benefit for patients with grade 3 tumors receiving vaginal brachytherapy.